Natural History of Adolescent Idiopathic Scoliosis in Skeletally Mature Patients: A Critical Review. Issue 12 (December 2015) - Agabegi, Steven S.; Kazemi, Namdar; Sturm, Peter F.; Mehlman, Charles T.
Abstract : The surgical treatment of adolescent idiopathic scoliosis is dependent on several factors, including curve type and magnitude, degree of curve progression, skeletal maturity, and other considerations, such as pain and cosmesis. The most common indication for surgery is curve progression. Most authors agree that surgical treatment should be considered in skeletally mature patients with curves >50° because of the risk of progression into adulthood. Furthermore, most authors would agree that curves measuring <40° to 45° in skeletally mature patients should be observed. When a skeletally mature patient with a curve measuring between 45° to 55° is presenting to an orthopaedic surgeon, it is not uncommon that the patient has no pain, no progression, and no imbalance. The generally accepted belief has been that curves that reach 50° are likely to progress into adulthood, progressing at a rate of 1° per year, based largely on the Iowa studies. However, the level of evidence for this is relatively weak, and the existing literature is equivocal in supporting the practice of performing surgery on these patients.